Genomic Imprinting and Cancer: From Primordial Germ Cells to Somatic Cells - Adele Murrell (The Scientific World Journal)
Imprinted genes are a subset of genes that are expressed from only one of the parental alleles. The majority of imprinted genes have roles in growth regulation and are, therefore, potential oncogenes or tumour suppressors. Cancer is a disease of aberrant cell growth and is characterised by genetic mutations and epigenetic changes such as DNA methylation. The mechanisms whereby imprinting is maintained in somatic cells and then erased and reset in the germline parallels epigenetic changes that cancer cells undergo. This review summarises what we know about imprinting in stem cells and how loss of imprinting may contribute to neoplasia.